2005
DOI: 10.1002/pbc.20654
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic findings of acute leukemia included in the Brazilian Collaborative Study Group of Infant acute leukemia

Abstract: Our results show that not only MLL rearrangements, but also other molecular abnormalities occur before birth and may contribute to leukemogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The most common genetic events occurring in children younger than 12 months, both in ALL and AML, are the rearrangements of the MLL gene on chromosome 11q23, which may be as high as 85% depending on the techniques applied (10,11). Infants diagnosed with acute leukemia harboring an 11q23 rearrangement have a particularly poor prognosis when compared to other children with acute leukemia (12).…”
Section: Clinical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common genetic events occurring in children younger than 12 months, both in ALL and AML, are the rearrangements of the MLL gene on chromosome 11q23, which may be as high as 85% depending on the techniques applied (10,11). Infants diagnosed with acute leukemia harboring an 11q23 rearrangement have a particularly poor prognosis when compared to other children with acute leukemia (12).…”
Section: Clinical Characterizationmentioning
confidence: 99%
“…For example, MLL rearrangement is associated with 90% of CD10 -cases but only with 20% of CD10 + cases. Also, the younger the child the higher is the frequency of MLL translocations (10,13). In series of IAL cases from different regions of Brazil, the comparison between age, immunophenotyping, and MLL rearrangements demonstrated that up to 14 months of age the pro-B subtype and the MLL-positive cases predominated (P < 0.0001), and among older cases, most of them were c-ALL and MLL-negative cases, as shown in Figure 1.…”
Section: Clinical Characterizationmentioning
confidence: 99%
“…The numbers of the main clinical and laboratory data were same as described previously (Emerenciano et al, 2006), but eight AML cases were excluded due to lack of birth weight records. Eight cases, which were misclassified in the previous report as biphenotypic leukaemia with aberrant phenotype, were then categorized as ALL in the present analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Details regarding case definition, control selection, exclusion criteria and data collection have been published previously (Emerenciano et al, 2006;Pombo-de-Oliveira et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of the fusion genes MLL/AF4, MLL/AF9 and MLL/ENL was assessed by RT-PCR, using conditions (Emerenciano et al 2006) and primers (Andersson et al 2001) previously described. Cell lines and known positive patients' samples were used as positive controls.…”
Section: Molecular Analysismentioning
confidence: 99%